Short-Term, Low-Volume Training Improves Heat Acclimatization in an Operational Context - Charlot, Keyne; Tardo-Dino, Pierre-Emmanuel; Buchet, Jean-François; Koulmann, Nathalie; Bourdon, Stéphanie; Lepetit, Benoit; Roslonski, Martin; Jousseaume, Loïc; Malgoyre, Alexandra (Frontiers in Physiology, 2017)
Personnel who travel to areas with a hot climate (WBGT > 27°C) may suffer from the heat (physiological strain, thermal discomfort, increased probability of heat illness), making them partially or fully inoperative. Performing physical activities during heat acclimatization is known to improve this process (i.e., improve measures of acclimatization for the same duration of acclimation). However, it is unknown whether such training would be efficient in an operative context, characterized by a high volume of work-related physical activity. Thirty French soldiers (Training group, T) performed a short (5 days), progressive, moderate (from three to five 8-min running sets at 50% of the speed at VO2max for 32–56 min) aerobic training program upon arriving at their base in United Arab Emirates ( 40°C and 12% RH). A control group (30 soldiers; No Training, NT) continued to perform their usual outdoor military activities ( 6 h.d−1). A field heat stress test (HST; three 8-min running sets at 50% of the speed at VO2max) was performed, before and after the heat acclimatization period, to assess physiological and subjective changes. Rectal temperature, heart rate (HR), thermal discomfort at rest and at the end of exercise, rates of perceived exertion (RPE), and sweat loss and osmolality decreased following heat acclimatization in both groups. However, the decreases in the T group were larger than those in the NT group for HR at the end of exercise (−20 ± 13 vs. −13 ± 6 bpm, respectively, p = 0.044), thermal discomfort at rest (−2.6 ± 2.7 vs. −1.4 ± 2.1 cm, respectively, p = 0.013) and at the end of exercise (−2.6 ± 1.9 vs. −1.6 ± 1.7 cm, respectively, p = 0.037) and RPE (−2.3 ± 1.8 vs. −1.3 ± 1.7, respectively, p = 0.035). Thus, we showed that adding short (<60 min), daily, moderate-intensity training sessions during a professional mission in a hot and dry environment accelerated several heat-acclimatization-induced changes at rest and during exercise in only 5 days.